2009
DOI: 10.1093/aob/mcp211
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of petal epidermal micromorphology in Leguminosae and its use as a marker of petal identity

Abstract: Strong micromorphological variation between different petals in the flower is exclusive to the subfamily Papilionoideae. Both major and minor epidermal types can be used as micromorphological markers of petal identity, at least in papilionoids, and they are important characters of flower evolution in the whole family. The molecular developmental pathway between specific epidermal micromorphology and the expression of petal identity genes has yet to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 43 publications
3
68
0
4
Order By: Relevance
“…Studies on the petal and sepal epidermal micromorphology of leguminous species are rather limited (Christensen and Hansen, 1998;Hammett et al, 1994;Ojeda et al, 2009;Stirton, 1981). Stirton (1981) examined the lateral petals of the papilionoids.…”
Section: Petal Micromorphologymentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on the petal and sepal epidermal micromorphology of leguminous species are rather limited (Christensen and Hansen, 1998;Hammett et al, 1994;Ojeda et al, 2009;Stirton, 1981). Stirton (1981) examined the lateral petals of the papilionoids.…”
Section: Petal Micromorphologymentioning
confidence: 99%
“…Stirton (1981) examined the lateral petals of the papilionoids. Hammett et al (1994) reported the epidermal type of the dorsal and lateral petals in 2 Lathyrus species, and Ojeda et al (2009) reported the epidermal types on the dorsal, lateral, and ventral petals of 7 species of the same genus. Except for L. sativus, the petal, and sepal micromorphology of L. chloranthus, L. digitatus, L. laxiflorus subsp.…”
Section: Petal Micromorphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, some mutants of floral symmetry, such as the peloric mutant in the snapdragon and toadflax, have been reported (Gustafsson, 1979;Luo et al, 1996;Cubas et al, 1999), and there have been some studies on developmental genetics using floral mutants (Yaxley et al, 2001;Benlloch et al, 2003), which have supported the idea that several genes control floral zygomorphy in papilionoid flowers. In addition, Ojeda et al (2009) indicated that epidermal cell shape of petals was different among standard, wing and keel of papilionoid flowers. Considering these results, we hypothesised that the changing number, size and shape of the cells in petals of papilionoid flower implies that the genetic factors involved are more complicated than those in the snapdragon.…”
Section: Complicated Changing Pattern Of Petal Cells Of Papilionoid Fmentioning
confidence: 99%